KEBIJAKAN KETERTIBAN DALAM TERMINAL PENUMPANG HAMID RUSDI - Safi‘i, Safi‘i; Widodo, Ernu; Ariwibawa, Muhammad Yustino (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This normative legal research examines Order Policy at the Hamid Rusdi Passenger Terminal by analyzing the applicable legal framework and its implementation. The primary focus of this study is to identify and analyze the roles and authorities of the Head of the Technical Implementation Unit for the Management of Transportation Infrastructure and Road Traffic (UPT P3 LLAJ) in Malang in enforcing order at the Hamid Rusdi Passenger Terminal, as stipulated in East Java Governor Regulation No. 54 of 2018. This research also investigates the philosophical foundation of order from legal and public policy perspectives, highlighting the principles of justice, legal certainty, and utility. The findings indicate that order policy at the terminal is a vital instrument integrated within Law No. 22 of 2009 concerning Road Traffic and Transportation (UU LLAJ). The study concludes that the enforcement of order at passenger terminals, led by strategic officials such as the Head of UPT P3 LLAJ Malang, is not merely for discipline and repressive control, but also serves as an essential public service aimed at enhancing the efficiency, safety, and comfort of transport users